Organizational Role Stress Among Public and Private Sector Employees: A Comparative Study - Bushara Bano; Rajiv Kumar Jha (The Lahore Journal of Business)
The aim of this study is to explore the differences in job-related stress, if any, between public and private sector employees, based on ten role stressors. It also examines the role of demographic variables on the stress levels of both public and private sector groups. Our methodology entails a survey of 182 public and 120 private sector employees in Uttar Pradesh, India, whose responses are measured according to an occupational role stress scale. We also use secondary data provided by the literature review. The sample was collected through convenience sampling. On applying the t-test and ANOVA test to the data, we find that both public and private sector employees face moderate levels of stress. While there is no significant difference overall between public and private sector employees in terms of total stress levels, certain individual stressors—such as work experience and educational qualifications—do yield differences. The major limitation of this study is that it was conducted in Uttar Pradesh alone, while the work culture of organizations other than in Uttar Pradesh may be different.